PENGARUH PERTUMBUHAN PENJUALAN DAN RETURN ON EQUITY TERHADAP PERUBAHAN LABA PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2015 - Intan Sari; M Anang Firmansyah; Budi Wahyu Mahardhika (UMSurabaya Publishing, 2016)
ABSTRACT This study aims to determine and analyze the effect of sales growth and return on equity simultaneously toward profit changes at coal mining companies listed on the Indonesia Stock Exchange 2010-2015, and the dominant influence on changes in earnings at coal mining companies listed on the Indonesia Stock Exchange 2010-2015. The population of this study was 21 coal mining companies listed on the BEI (Indonesia Stock Exchange). Sampling technique used purposive sampling method with criteria. The sample of this study was as many as 10 companies. The analysis method of this study used multiple linear regressions by using SPSS 20. The research results showed that the growth of sales and return on equity affect simultaneously the profit changes. Partially, sales growth influences the profit changes because thitung 2,960 >ttable 2,002, while return on equity does not affect profit change because thitung 0,110 < ttable2,002. Variable of sales growth has dominant influence to profit change with highest regression coefficient value of 0,366 among independent variables influencing variable dependent. Keywords : Sales Growth, Return on Equity, and Profit ChangeCorrespondence to : intansari634@gmail.com, anangfirmansyah.61@gmail.com, budi.w.mahardhika@gmail.com